TRADISI KEINTELEKTUALAN DAN BIOGHRAFI DAN PEMIKIRAN NURCHALISH MADJID - Fakhrurrazi Fakhrurrazi (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2021)
Thinking that is progressive and useful for the general public is very much needed. It is for the sole sake of progress in the community. However, the problems in society are so complex that certain groups want to change. One of the most famous figures in Islam is Nurchalish Madjid, famous for his renewal model. The thoughts of Cak Nur (Nurcholis Madjid) are identical to Islam, Indonesianness and modernity. He was the first character to express this; Saifullah said in Pena Almuslim, "Marriage of Islam, modernity. Nurchalish Madjid first put forward this idea in the era of the 70s, and now it is felt the importance of the idea being actualized in the context of building the nation's character". During the post-independence governance debate that is still unfinished, Nurchalish Madjid and his fellow Islamic thought reformers must come face-to-face to hold their ideas accountable to society and their scholarship.